Enhanced multicolor optomechanically induced transparency in electro-optical hybrid system. (1st July 2022) - Pan, Guixia; Xiao, Ruijie; Zhai, Chengbo
Abstract: We investigate the tunable multicolor optomechanically induced transparency through electro-optical hybrid system. The system consists an optical cavity fulled with three-level atomic ensemble and two charged mechanical oscillators coupled via Coulomb interaction. Under different coupling strengths, the system can exhibit the phenomena of optomechanical induced transparency increase. Specifically, the number of the transparency windows increases with the presence of charged mechanical resonators and atoms. Furthermore, the induced transparency phenomena are strongly manipulated by the coupling strength between the optical mode and the mechanical mode, or between the optical mode and the atoms and the Rabi frequency, or between the Coulomb coupling between the two charged mechanical modes. It is found that the larger coupling strength between the cavity field and the atoms and the mechanical oscillator, the wider transparent windows. Our approach is feasible for storage of light and has potential applications in quantum information processing.